Cryosurgery of focal liver diseases - B. I. Alperovich; N. N. Merzlikin; V. N. Salo; L. M. Paramonova; M. A. Maksimov; M. B. Saipov; I. M. Yeskov (Бюллетень сибирской медицины, 2011)
The results of cryosurgical treatment of 339 patients with various focal liver diseases are presented. The experience of using cryosurgical equipment designed and manufactured in the Tomsk Hepatological Center in the surgery of focal liver diseases is analyzed. The application of inventive instruments in the liver resection leads to a decrease in the intraoperative blood loss down to 30- 40% and favors the reduction of backsets, because the cryodestruction of liver stump after resection leads to the destruction of rest parts of parasitic tissue in the surgical zone. The use of cryosurgical techniques lowers the number of deaths down to 4.42%.